“The 19th century World Exhibitions and their Photographic Memories. Between Historicism, Exoticism and Innovation in Architecture” - Souto, Maria Helena (2012)
The series of World Exhibitions that occurred in the second half of the 19th century was essential to the dissemination and popularization of technical advances. The photography, one of the novelties, played a precise and fundamental role right from the beginning: the first world exhibition held in London in 1851 at the Crystal Palace, gave great visibility to photographic practices through the exhibition of this new technique, as well as through photographic surveys of the exhibition itself. Furthermore, photographic techniques allowed the presentation of images from several countries, thus introducing new landscapes, people and artistic culture. This paper aims to analyse how the photography and the photographers - both the anonymous as well as the well known, like Aurélio da Paz dos Reis, one of the photography and cinema pioneers’ in Portugal – contributed on one hand to the display of Portugal in the World Exhibitions and, on the other hand to the dissemination of the images of World Exhibitions through newspapers and magazines. A special attention will be given to the Portugal’s pavilions. Since the World Exhibition of 1867, Paris materialized a new kind of exposition where the National Pavilions, became one of the most important attraction to the visitors. These pavilions offered the idea of a world museum and simultaneously, introduced new references for the architects of eclecticism, to whom the exhibitions were places for manipulation and experimentation. On a whole the pavilions were designed following models of national architecture likely to be easily recognized abroad. Such is the case of the Portuguese Pavilions and this paper analysis how Portugal with its evocative imagery of the discoveries give an image of wealth and exoticism, associable to the mythical times of glory of former Portuguese Empire.